Urinary Bladder Mullerianosis Causing Recurrent Abdominal Pain: A Rare Case Report and Review of the Literature - Kumar, Manjeet; Barwal, Kailash Chander; Sharma, Girish Kumar; Mardi, Kavita; Raina, Pamposh; Sharma, Sanjeev (Journal of Health and Allied Sciences NU, 2023)
Mullerianosis of the urinary bladder is a rare bladder lesion with fewer than 30 cases reported in the literature. It describes the ectopic presence of endocervical, endometrium, and endosalpingial tissues inside the urinary bladder. It is diagnosed when at least two of three Mullerian tissues, endometriosis, endocervicosis, and endosalpingiosis, are identified. Mullerianosis presents in females of the reproductive age group, especially after pelvic surgery. Treatment involves resection of the bladder mass and ruling out malignant pathology. Follow-up of Mullerianosis is vital, as recurrence is common. Medical therapy is also indicated when a diagnosis is established after the histopathological examination of the tumor.We report a 31-year-old female presenting with recurrent lower abdominal pain. Cystoscopy showed a mass of 3 × 3 cm in the urinary bladder. Transurethral resection of bladder tumor was resected, and histopathology suggested a combination of endometriosis, endocervicosis, and endosalpingiosis. Pain was resolved after surgery, but the lesion recurred at 3 months, which was subsequently resected.
Keywords: Mullerianosis; urinary bladder; transurethral resection of bladder